(untitled) (Educational Perspectives Magazine (REPED), 2023)
The context of globalization is transforming the process of interaction both for individuáis and for institutions: Migrations within the third cycle tum an important group of students who are studying for a doctoral degree outside their own countries, into expatriates. The professionals who go abroad to specialize in their third cycle studies cause an effect on the societies they go to. Likewise, they are affected by this new society when they are not accepted. This study reveáis the institutional contexts the students encounter, as well as the objective and subjective life experiences of the students while they go through that process. This allowed to develop a Cultural Shock Model in order to understand and tackle with a sounder basis the conflicts of intercultural nature experienced by intemational students.